Application of Independence Land Use with Contemporary Architecture Approach in Human Rights History Museum - Miftakhul Maulidyah Ulfatah; Wiwik Widyo Widjajanti; Randy Pratama Salisnanda (Journal of Civil Engineering, Planning and Design, 2023)
Indonesia is a state of law that has a recognition to protect the rights of every citizen, every human being has the right to live, grow and develop without discrimination. Surabaya is a city that has a lot of history as well as being the capital of East Java Province and the second largest city in Indonesia. The design location is on Dr. Ir. Soekarno (Merr) street, Surabaya City. Human rights are owned by all human beings from birth and are valid for life, but human rights currently tend to be ignored, so that many people do not get their rights fairly, there is no mutual respect, are oppressed and treated inhumanely in violation of existing norms. Using descriptive and qualitative methods to determine case studies. The selection of the theme of Contemporary Architecture with the macro concept of Independence which means free or independent, so that the design of the Human Rights history Museum design applies freedom of work but still adheres to existing norms. The design result of the transformation of the land concept results in a micro-landscape that is extensive and has a wide-reaching nature. With the existence of the Museum of Human Rights History, it is hoped that it can become a means of education and knowledge for all groups, both for the public, students, and students so that they can respect each other regardless of differences in any aspect to raise awareness of the importance of Human Rights as a message of peace to be free in accordance with the norms of Pancasila.